Inquiry into recruitment and employment in the meat and poultry processing sector. Report of the findings and recommendations (London, 2010)
"The inquiry, which spoke to 260 workers, found physical and verbal abuse were not uncommon, with a fifth of workers interviewed reporting being pushed, kicked or having things thrown at them by line managers. Workers also reported being refused permission to take toilet breaks, and subsequently urinating or bleeding on themselves at the production line. A quarter of those interviewed said they had witnessed mistreatment of pregnant workers, such as the instant dismissal of agency workers who had announced they were pregnant. Pregnant women were also forced to continue to undertake work that posed risks to their health and safety, including heavy lifting and extended periods of standing. "